2002
DOI: 10.1046/j.0902-0055.2001.00100.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and immunological evidence of oral Treponema in the human brain and their association with Alzheimer's disease

Abstract: The purpose of this investigation was to use molecular and immunological techniques to determine whether oral Treponema infected the human brain. Pieces of frontal lobe cortex from 34 subjects were analyzed with species-specific PCR and monoclonal antibodies. PCR detected Treponema in 14/16 Alzheimer's disease (AD) and 4/18 non-AD donors (P < 0.001), and AD specimens had more Treponema species than controls (P < 0.001). PCR also detected Treponema in trigeminal ganglia from three AD and two control donors. Cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
359
1
8

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 326 publications
(375 citation statements)
references
References 21 publications
7
359
1
8
Order By: Relevance
“…In addition, B. burgdorferi specific antigens were co-localized with Aβ deposits and glial and neuronal cells exposed to B. burgdorferi were able to produce amyloid beta precursor protein and hyperphosphorylated tau proteins [81], suggesting that B. burgdorferi is able to induce AD specific pathology. Of interest, spirochetes from the oral cavity have been reported by Riviere in brain samples from AD patients were using molecular and immunological methods [101]. These results suggest, as did Miklossy's results that spirochetes within brain tissue may originate from diverse areas including the oral cavity [78].…”
Section: Peripheral Infection and Alzheimer's Diseasesupporting
confidence: 61%
See 1 more Smart Citation
“…In addition, B. burgdorferi specific antigens were co-localized with Aβ deposits and glial and neuronal cells exposed to B. burgdorferi were able to produce amyloid beta precursor protein and hyperphosphorylated tau proteins [81], suggesting that B. burgdorferi is able to induce AD specific pathology. Of interest, spirochetes from the oral cavity have been reported by Riviere in brain samples from AD patients were using molecular and immunological methods [101]. These results suggest, as did Miklossy's results that spirochetes within brain tissue may originate from diverse areas including the oral cavity [78].…”
Section: Peripheral Infection and Alzheimer's Diseasesupporting
confidence: 61%
“…For example, Treponema species including T. denticola were detected in 14/16 AD and 4/18 non-AD brains. In addition, AD specimens also had more Treponema species than controls [101]. In an animal model of oral infections T. denticola was detected postmortem in the brain [30].…”
Section: Association Between Periodontal Disease and Progression Of Amentioning
confidence: 98%
“…Recent biochemical, biophysical, and imaging analyses revealed that fibers produced by E. coli, termed "curly" were composed of amyloid [5]. It was suggested that several types of spirochetes may be involved in AD, and also that amyloidogenic proteins may be an integral part of spirochetes, which may, therefore, play a role in amyloidogenesis in AD [18][19][20][21][22][23][24][25]31]. Furthermore, it was shown that the OspA outer surface protein of B. burgdorferi forms amyloid fibrils in vitro, similar to human amyloid [26].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, it is known to cause a strong inflammatory response. In addition, the interesting finding is that a periodontal disease-related bacteria of the Treponema genus was found in the trigeminal ganglion, brainstem, and cerebral cortex; its frequency is said to be high in patients with AD in particular [6]. This finding suggests that periodontal disease-related bacteria can be directly transmitted into the brain and cause inflammation.…”
Section: Periodontal Disease and Admentioning
confidence: 69%
“…To date, periodontal disease has been reported as a risk factor for diabetes mellitus (DM), cardio-and cerebrovascular disease, aspiration pneumonia, premature and low birth weight infants, bacterial endocarditis, glomerulonephritis, arthritis, and palmoplantar pustulosis [1][2][3][4][5]. The following three pathways are assumed to be the mechanism of the systemic spread of periodontal disease: direct action of bacterial body and toxin of periodontal disease-related bacteria at the local periodontal site that spread to target organs through the hematogenous route or respiratory tract [4]; the action of inflammation-inducing substances such as cytokines, which are produced by the inflammatory response within periodontal tissue or immune response that spread hematogenously to the target organs [5]; and a pathway that results in intracerebral spread through the nervous system [6,7]. There are various data on intravascular infiltration of periodontal disease-related bacteria and its spread to target organs thus far, but its mechanism of affecting diseases is not fully understood.…”
Section: Introductionmentioning
confidence: 99%